2013
DOI: 10.1098/rsob.130021
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a bacterial putative acetyltransferase defines the fold of the human O -GlcNAcase C-terminal domain

Abstract: The dynamic modification of proteins by O-linked N-acetylglucosamine (O-GlcNAc) is an essential posttranslational modification present in higher eukaryotes. Removal of O-GlcNAc is catalysed by O-GlcNAcase, a multi-domain enzyme that has been reported to be bifunctional, possessing both glycoside hydrolase and histone acetyltransferase (AT) activity. Insights into the mechanism, protein substrate recognition and inhibition of the hydrolase domain of human OGA (hOGA) have been obtained via the use of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 66 publications
(113 reference statements)
1
45
0
Order By: Relevance
“…Hayakawa et al over-expressed OGA in emybryonic stem cells (ESC) and observed a decreased HAT activity toward H3 K14 and H4 K8 upon Thiamet-G treatment or with the expression of OGA D175A , which also showed a significant decrease in O-GlcNAcase activity [17], suggesting that O-GlcNAcase activity is required for HAT activity in vivo . Conversely, a structural study of the HAT domain of human OGA has shown that it shouldn’t be able to bind Acetyl-CoA [18]. Since recombinant OGA purified from bacteria acetylated H3 K14 and H4 K8 but only when pre-incubated with mammalian cell lysates [16], it is then possible that the observed HAT activity could be due to interaction and activation with a third HAT.…”
Section: Oga a Histone Acetyltranferase?mentioning
confidence: 99%
“…Hayakawa et al over-expressed OGA in emybryonic stem cells (ESC) and observed a decreased HAT activity toward H3 K14 and H4 K8 upon Thiamet-G treatment or with the expression of OGA D175A , which also showed a significant decrease in O-GlcNAcase activity [17], suggesting that O-GlcNAcase activity is required for HAT activity in vivo . Conversely, a structural study of the HAT domain of human OGA has shown that it shouldn’t be able to bind Acetyl-CoA [18]. Since recombinant OGA purified from bacteria acetylated H3 K14 and H4 K8 but only when pre-incubated with mammalian cell lysates [16], it is then possible that the observed HAT activity could be due to interaction and activation with a third HAT.…”
Section: Oga a Histone Acetyltranferase?mentioning
confidence: 99%
“…Therefore, O -GlcNAcylation would be able to regulate the acetylation of the histones tails, but this function remains controversial (35). Whisenhunt et al demonstrated that OGA/NCOAT, OGT, the co-repressor Sin3A (Switch-independent 3A), and HDAC1 (Histone Deacetylase 1) co-exist in a complex that was named O -GlcNAczyme (36).…”
Section: O-glcnacylation: a Nutrient Sensor Regulating Chromatin Dynamentioning
confidence: 99%
“…One of these contains a domain with similarities to a histone acetyltransferase domain but lacking the critical residues for catalytic activity. This has been termed a pseudoHAT domain (41). The other major O-GlcNAcase isoform has a 14-amino extension that serves to target it to lipid droplets.…”
Section: The Enzymes Of O-glcnac Cyclingmentioning
confidence: 99%